Effect of Topical Administration of Tranexamic Acid in Reducing Post-Operative Bleeding after Off-Pump Coronary Artery Bypass Surgery-A Single Center Experience (Cardiovascular Journal, 2017)
Background: This study was designed to assess the role of topically applied tranexamic acid in pericardial cavity in reducing post operative bleeding.Methods: This study is a non-randomized, double blinded, clinical trial, conducted in the Department of Cardiac Surgery, National Institute of Cardiovascular Diseases from January 2014 to December 2015 among the patients admitted for off pump coronary artery bypass (OPCAB) surgery. A total of 60 patients were recruited for the study and they were divided in two groups- 30 patients in tranexamic acid group (Group I) and 30 patients in placebo group (Group II). On completion of the grafting, before closure of the sternum tranexamic acid (2.5 g/25 ml) or placebo (25 ml of saline) diluted in 100 ml of warm saline (37 °C) was instilled into the pericardial cavity including the mediastinal tissues and left for 5 minutes. Total mediastinal bleeding and packed red cell transfusion were estimated in the postoperative period in both groups.Results: There was no significant difference noted in baseline demographic data, basic clinical characteristics and preoperative coagulation profile between the 2 groups (P > 0.05). Total mediastinal bleeding and packed red cell transfusion in group I and group II patients was 421.67±70.32vs 593.33±77.38ml, p